الاتصال الرقمي وتحسين الخدمة في الوسط الطلابي " دراسة عينة من الطلبة مستخدمي الفضاء الرقمي - فقريش, نوارة; بن ناصر, توفيق (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2021)
Through this study, we are trying to clarify concepts about information and communication technology in the higher education sector in light of the changes and developments taking place in the Sports Administration and Management Department , To achieve the objectives of this study, we used the descriptive and analytical approach appropriate to the research topic, by highlighting the role of information and communication technology in developing creative management thinking among students of the Department of Sports Administration and Management at the University of Msila. To achieve this, we divided the study into two main aspects, one theoretical and the other practical. The first included a conceptual approach to information and communication technology and management thinking The second aspect of it revolved around the role of information and communication technology in developing management thinking, Where it was found that there is a great role that information and communication technology plays by creating new cultures that contribute to the development of students' management thinking, and that they contribute significantly to the theorizing and framing of students. Finally, the research concludes with several conclusions and future hypotheses that can contribute to supporting the scientific research of students of the Department of Sports Administration and Management at the University of Msilaالاتصال الرقمي وتحسين الخدمة في الوسط الطلابي " دراسة عينة من الطلبة مستخدمي الفضاء الرقمي" نحاول من خلال هذه الدراسة تمعالجة موضوع الاتصال الرقمي وتدوره في تحسين الخدمة في الوسط الطلابي مع اختيارنا درتسة عينة من الطلبة مستخدمي الفضاء الرقمي كنموذج للدراسة باعتبار الاتصال الرقمي أحد الركائز التي أصبحت تعتمد عليها المؤسسات الجامعية في تحسين وتطوير أدائها بصفة عامة، فتناولت هذه الدراسة الموضوع من جانب مفهوم الاتصال الرقمي وتأثيره على الطلبة داخل الفضاء الجامعي وكذلك للأهمية التي يكتسبها، وخلال دراستنا أسقطنا هذا الموضوع على الطلبة الجامعيين لمحاولة التعرف على أثر الاتصال الرقمي على الطبلة الدارسين بجامعة المسيلة، خاصة وأن الاتصال الرقمي يعد بمثابة اللبنة الأساسية التي يطل من خلالها الطلبة على الجامعة وكذا العالم الدراسي وفي نفس الوقت يتواصلون بها . وقد قمن افي دراستنا بوصف وتحليل النتائج والمعلومات المتوصل إليها وان اختيارنا لهذا الموضوع لم يكن عشوائيا بل كان نتيجة لعدة أسباب من بينها أهمية الموضوع عند الطلبة وحداثته . وقد توصلت الدراسة إلى أن الاتصال الرقمي يمثل قناة اتصالية بين الإدارة والطلبة ويعد من أهم المنافذ الجديدة التي أصبحت الجامعات تقدم من خلالها الخدم الجامعية وتستغلها لفهعيل التواصل مع الطلبة الجامعين ، وهذا لما لها من مميزتا وخصائص وسمات جعلتها أمثر تأثيرا وفاعلية
Keywords: الاتصال الرقمي، الطبة ، الخدمةinformation technology, management thinking, administration and .sports management department